2008
DOI: 10.1016/j.ecresq.2007.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Structural and process features in three types of child care for children from high and low income families

Abstract: We use observations from the NICHD Study of Early Child Care and Youth Development (SECCYD) to compare structural and process characteristics of child care centers, family child care homes (nonrelative care in a home setting) and care by relatives for 2, 3-and 4 ½-year-old children. Type of care differences in structural and caregiver characteristics were consistent across ages: centers had higher child-to-adult ratios and bigger groups; centers had caregivers with better education, more training in early chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
124
1
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(136 citation statements)
references
References 38 publications
7
124
1
4
Order By: Relevance
“…These results document continuing inequity in access to quality of care for low-income children, in this study defined as those living in families between 100% and 200% of the FPL. These results are consistent with other studies documenting a "U" shaped curve in the associations between family income and child care quality, with the caveat that previous studies have variously defined low, middle, and higher-income families (e.g., Dowsett et al, 2008;NICHD ECCRN, 2000;Phillips et al, 1994).…”
Section: Family Income Parents' Perceptions Of Quality and Observedsupporting
confidence: 91%
See 1 more Smart Citation
“…These results document continuing inequity in access to quality of care for low-income children, in this study defined as those living in families between 100% and 200% of the FPL. These results are consistent with other studies documenting a "U" shaped curve in the associations between family income and child care quality, with the caveat that previous studies have variously defined low, middle, and higher-income families (e.g., Dowsett et al, 2008;NICHD ECCRN, 2000;Phillips et al, 1994).…”
Section: Family Income Parents' Perceptions Of Quality and Observedsupporting
confidence: 91%
“…Phillips et al (1994) reported that teachers in community-based centers serving predominantly low-income children were more detached and harsh and less sensitive than teachers in centers serving poorer or more-affluent children, and that quality of care in centers serving upper-income children was the most consistently positive in terms of caregiving and developmentally appropriate activities. Dowsett, Huston, Imes, and Gennetian (2008) reported a curvilinear association between family income and structural quality in center-based programs, but a linear association between family income and process quality. Programs serving primarily low-income children tend to employ teachers with less education and compensate them more poorly than programs serving middle-and upper-income children, and structural indicators of quality are significantly better in programs serving upper-income children (Marshall et al, 2003;Sachs, 2000).…”
mentioning
confidence: 97%
“…For example, it was shown in the NICHD SECCYD that caretakers in informal relative settings were generally less educated and offered lower levels of stimulation than ones in formal childcare (Dowsett, Huston, Imes, & Gennetian, 2008). Whereas we have no information on levels of quality in informal childcare for the QLSCD, the quality of formal childcare (that is, non-relative center-based and non-relative out-of-home) in Quebec, Canada has been rated as moderate (Japel, Côté, & Tremblay, 2005), and similar to that of several other industrialized countries (i.e., United States, Germany, Portugal, and Spain) (Egeland & Hiester, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing child care use across income groups find inconsistent differences in the quality of center-based care, with some research pointing to higher quality among low-income children (NICHD, 1997;Phillips et al, 1994) and others finding lower quality (Loeb et al, 2004;Marshall et al, 2001). Research by Dowsett et al (2008) finds that structural measures of child care quality are about equal for low-and high-income children, but that poor children experience lower quality care across several process-oriented measures, including negative adult interactions and cognitive stimulation. The quality of family-based and relative care, however, is more consistently of lower quality among low-income children (Coley et al, 2001;Dowsett et al, 2008;Votruba-Drzal et al, 2004).…”
mentioning
confidence: 99%
“…Research by Dowsett et al (2008) finds that structural measures of child care quality are about equal for low-and high-income children, but that poor children experience lower quality care across several process-oriented measures, including negative adult interactions and cognitive stimulation. The quality of family-based and relative care, however, is more consistently of lower quality among low-income children (Coley et al, 2001;Dowsett et al, 2008;Votruba-Drzal et al, 2004).…”
mentioning
confidence: 99%